Clinical and radiological results of final fusion in patients who underwent lengthening with magnetically controlled growing rods. About 66 patients with a mean follow-up of 5 years - Mainard, Nicolas; Saghbini, Elie; Langlais, Tristan; Vialle, Raphael; Nectoux, Eric; Sales de Gauzy, Jerome; Fron, Damien; Canavese, Federico (European spine journal, 2023)
Purpose The aim of this study was to evaluate the effects of definitive arthrodesis on frontal and sagittal spine balance in EOS patients treated with MCGR, as well as the complications associated with this procedure and the outcome at last follow-up. Methods This was a multicentre study in 10 French centres. All patients who underwent posterior spinal arthrodesis after completion of MCGR treatment, regardless of age, etiology of scoliosis between 2011 and 2022, were included. Results A total of 66 patients who had a final fusion after the lengthening programme were included in the study. The mean follow-up time was 5.5 ± 1.7 years (range: 2.1–9). The mean follow-up time after arthrodesis was 24 ± 18 months (range: 3–68) and the mean age at arthrodesis was 13.5 ± 1.5 years (range: 9.5–17). The main and secondary curves were significantly ( p < 0.005 and p = 0.03) improved by arthrodesis (16.4° and 9° respectively) and stabilised at the last follow-up. The T1-T12 and T1-S1 distances increased by 8.4 mm and 14 mm with spinal fusion, with no significant difference ( p = 0.096 and p = 0.068). There was no significant improvement in the rest of the parameters with arthrodesis, nor was there any significant deterioration at last follow-up. After final fusion, there were a total of 24 complications in 18 patients (27.3%) that routinely led to repeat surgery. Conclusion Final fusion after MCGR provides satisfactory additional correction of the main and secondary curves and a moderate increase in the T1-T12 distance but has no impact on sagittal balance and other radiological parameters. The post-operative complication rate is particularly high in patients at risk of complications. Level of evidence Level 4.